Advances in organometallic chemistry. - Fink, Mark J.; Hill, Anthony F.; West, Robert, 1928- (Advances in organometallic chemistry, 2008)
Almost all branches of chemistry and material science now interface with organometallic chemistry - the study of compounds containing carbon-metal bonds. This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field which has expanded enormously since the publication of Volume 1 in 1964.